PENGARUH EKSTRAK SAMBILOTO (Andrographis paniculata Nees.) TERHADAP DAYA SEKSUAL MENCIT JANTAN (Mus musculus L.) SWISS WEBSTER - Penatriwati, Penatriwati; Sumarmin, Ramadhan; Widiana, Rina (STKIP PGRI Sumbar, 2013)
ABSTRACT Sambiloto(Ind) or Bitter(Eng) Andrographis paniculata Nees., is one of the traditional medicinal herb expected to be antifertility. It contain flavonoids and lactones. Lactone compound containing andrographolide which is the active ingredient of the plant that acts as antifertility. Andrographolide serves to prevent cell division (cytokinesis). This study aimed to determine the effect of extract of Bitter (Andrographis paniculata Nees.) to the sexual endurance of male mice (Mus musculus L.) Swiss Webster. This study uses CRD (Completely Randomized Design), 4 treatments each treatment consisted of 6 adult mice and watered ad libitum. The control, without any bitter extract and treatment II, III and IV were treated with Bitter extract orally for 36 days with a dose of 0.2 g/head/day, 0.4 g/head/day and 0,6 g/head/day. After that, mating test on each test animals treated with 1 male mice mated with female mice 5 to see the amount of movement intromisi, the number off female mated and the number of pregnant mice. The results obtained were analyzed using ANOVA (Analysis of Variance). The data analysis to obtain intromition average at 16.16 control, treatment of 0.2 g with an average of 14.16, 0.4 g treatment with an average of 6.33 and 0.6 g treatment on average 6.66, indicating a decrease in the number of intromition than the control treatment. For the number of mated high on average at 2.5 head control, treatment of 0.2 g on average 2.33 head, 0.4 g treatment on average 2.16 head and 0.6 g treatment an average of 2,00 while the number of pregnant mice were successfully obtained an average of 2.33 head in the control, treatment of 0.2 g on average 2 head, treatment of 0.4 g on average 1.16 head and 0.6 g treatment on average 1.33 head. It can be concluded that the extract of Bitter (Andrographis paniculata Nees.) affect the sexual endurance of male mice (Mus musculus L.).